Macroeconomics and finance in the Caribbean : quantitative analyses - Worrell, DeLisle, ed. (Caribbean Centre for Monetary studies St. AugustineTT, 1997)
Reflects current understanding of economic processes in the Caribbean. Concerns range through macroeconomic modelling, macroeconomic policy, the effects of external shocks, the efficacy of monetary targets, the roots of inflation, the relationship of government expenditure to growth, risk and return in securities markets and the quality and characteristics of data.